Sous la conduite d’Hermès, aux carrefours de la traduction et du féminisme - Jane Elisabeth Wilhelm (Glad!)
We will examine in this paper the meeting points of translation, hermeneutics and feminism, invoking in particular Paul Ricœur's “paradigm of translation” and his concept of linguistic hospitality. Philosophical hermeneutics, in its political dimension, allows us to acknowledge the partiality of our understanding and to support feminist arguments regarding the interpretative dimension of difference. Translation, for Ricœur, poses an ethical problem and he also invites us to transpose the model of linguistic hospitality in terms of political imagination. The paradigm of translation could consequently expand to the translation of patriarchal culture and its sexist representations, among which sexual metaphors, by its decentering to allow for the language and the reality of women while living together in equality.